Hierarchical urchin-like CoSe2/CoSeO3 electro-catalysts for dye-sensitized solar cells: up to 19% PCE under dim light illumination. Issue 45 (6th November 2019) - Huang, Yi-June; Chen, Han-Ting; Ann, Shiuan-Bai; Li, Chun-Ting; Lin, Jiann T.; Lee, Chuan-Pei; Ho, Kuo-Chuan
Abstract : A hierarchical urchin-like structure of CoSe2 /CoSeO3 (denoted as CoSe2 /CoSeO3 -UL) is synthesized by a one-step hydrothermal method and investigated as the electro-catalyst for the counter electrode (CE) of dye-sensitized solar cells (DSSCs). Abstract : A hierarchical urchin-like structure of CoSe2 /CoSeO3 (denoted as CoSe2 /CoSeO3 -UL) is synthesized by a one-step hydrothermal method and investigated as the electro-catalyst for the counter electrode (CE) of dye-sensitized solar cells (DSSCs). The evolution of the CoSe2 /CoSeO3 nanostructures as a function of the synthesis time has been identified by scanning electron microscopy. The growth mechanism is proposed and the desired CoSe2 /CoSeO3 hierarchical UL structure is noticed at 4 h. CoSe2 /CoSeO3 -UL consists of nanoparticles and hexagonal prisms for providing a high surface area for catalytic reactions and a one dimensional charge transport route, respectively. The results show that DSSCs using the CoSe2 /CoSeO3 -UL CE exhibit a higher power conversion efficiency ( η ) of 9.29 ± 0.24% than that of the cell using a Pt CE (8.33 ± 0.07%). Under various dim light conditions ( i.e ., a T5 lamp), the DSSC with the CoSe2 /CoSeO3 -UL CE shows outstanding η 's of 19.88 ± 0.10%, 18.24 ± 0.06%, and 16.00 ± 0.13% at 7000 lux (2.21 mW cm −2 ), 6000 lux (1.89 mW cm −2 ) and 4800 lux (1.55 mW cm −2 ), respectively. This study demonstrates that CoSe2 /CoSeO3 -UL has great potential to replace Pt in DSSCs, and the application of DSSCs can be extended from outdoor to indoor conditions.